2016
DOI: 10.1002/gcc.22361
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus‐mediated somatic recombination and development of a novel mouse model for sporadic colorectal cancer

Abstract: In this study, we have developed a novel mouse model for sporadic colorectal cancer (CRC) by utilizing APC conditional knockout (Apc(CKO) ) mouse and lentivirus encoding Cre recombinase and a reporter gene (EGFP or LacZ). Lentiviral transduction of colonic crypt stem cells allowed for the long-term expression of reporter gene as well as excision of floxed Apc alleles, which resulted in tumor development. Tumors represented adenoma stages along with the nuclear accumulation of β-catenin. Loss of E-cadherin at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, DSS was significantly worse in patients with RCC than in patients with distal CRC in the subgroups of patients who had stage III or IV disease, were 70 years or younger, or had non-mucinous adenocarcinoma. The predictive value of primary tumor location in survival among patients with metastatic CRC was confirmed in several latest studies[2528]. Chen et al revealed that right-sided tumor site was an independent predictor of shorter PFS (HR = 1.32, P = 0.0072) and OS (HR = 1.45, P = 0.0003) among 969 patients with KRAS wild-type CRC receiving Cetuximab therapy treatment[26].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, DSS was significantly worse in patients with RCC than in patients with distal CRC in the subgroups of patients who had stage III or IV disease, were 70 years or younger, or had non-mucinous adenocarcinoma. The predictive value of primary tumor location in survival among patients with metastatic CRC was confirmed in several latest studies[2528]. Chen et al revealed that right-sided tumor site was an independent predictor of shorter PFS (HR = 1.32, P = 0.0072) and OS (HR = 1.45, P = 0.0003) among 969 patients with KRAS wild-type CRC receiving Cetuximab therapy treatment[26].…”
Section: Discussionmentioning
confidence: 93%
“…We recently reported that JAG2 expression is up-regulated in colorectal tumors of Apc CKO mice resulting from transduction of colonic epithelium with Cre-encoding lentivirus [ 15 ]. To determine JAG2 expression in other mouse models of CRC, we analyzed JAG2 expression in the intestinal tumors of Apc Min /+ mice.…”
Section: Resultsmentioning
confidence: 99%
“…Constitutive activation of β-catenin signaling due to inactivating mutations in APC gene or activating mutations in β-catenin gene is a common feature of CRC. We previously have shown that JAG2 expression is increased in colorectal tumors of Apc CKO mice [ 15 ]. In the current study, we also observed increased JAG2 mRNA expression in the tumors of Apc Min /+ mice, while tumoral expression of other NOTCH ligands was variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in prognosis among RCC, LCC, and RECC patients is notable, with most studies confirming that RCC patients have poorer prognosis compared to patients with LCC and RECC (5,14,(18)(19)(20). Furthermore, the intestinal flora, clinical manifestations, and treatment responses of patients with RCC, LCC, and RECC vary considerably (18,19).…”
Section: Discussionmentioning
confidence: 99%